2021
DOI: 10.3390/rs13163191
|View full text |Cite
|
Sign up to set email alerts
|

How the Small Object Detection via Machine Learning and UAS-Based Remote-Sensing Imagery Can Support the Achievement of SDG2: A Case Study of Vole Burrows

Abstract: Small mammals, and particularly rodents, are common inhabitants of farmlands, where they play key roles in the ecosystem, but when overabundant, they can be major pests, able to reduce crop production and farmers’ incomes, with tangible effects on the achievement of Sustainable Development Goals no 2 (SDG2, Zero Hunger) of the United Nations. Farmers do not currently have a standardized, accurate method of detecting the presence, abundance, and locations of rodents in their fields, and hence do not have enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…The model training was stopped when the model was no longer improving. The following metrics were used to evaluate the classification model: precision (TP/(TP + FP)), recall (TP/(TP + FN) and F1-score 29 with “Compute Accuracy For Object Detection” tool in ArcGIS Pro. True Positives [TP] is the number of detections with intersection over union (IoU) > 0.5.…”
Section: Methodsmentioning
confidence: 99%
“…The model training was stopped when the model was no longer improving. The following metrics were used to evaluate the classification model: precision (TP/(TP + FP)), recall (TP/(TP + FN) and F1-score 29 with “Compute Accuracy For Object Detection” tool in ArcGIS Pro. True Positives [TP] is the number of detections with intersection over union (IoU) > 0.5.…”
Section: Methodsmentioning
confidence: 99%
“…Wan et al (2021) successfully detected grassland rat holes (unspecified species) using R-CNN and improved Single Shot MultiBox Detector (SSD). Ezzy et al (2021) detected Levant voles burrows (2.5-7.5 cm in diameter) in farmlands and found that YOLOv3 provided relatively accurate and robust results. Previous studies explored various algorithms to detect different rodent holes under various environments.…”
Section: Introductionmentioning
confidence: 99%
“…In regards to rodent populations, two main areas have been explored in the literature: (1) survey and recognition of rodent infestation; 11,18,19 and (2) automatic identification of rodent evidence, such as burrows, by following a featureextraction schema. 12,20 A third group of investigations explores objective assessments of the damaged areas caused by the rodents, but in this case, the research relies on remote sensing, mainly by the use of Moderate Resolution Imaging Spectroradiometer (MODIS) imagery. 21 Currently, very little scientific research exists on the combined use of UAS and multispectral imagery for assessments of rodents' impact on agricultural fields, and more specifically in relation to the common vole.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, there is scientific literature related to the use of drones and red/green/blue (RGB)‐based imagery for rodent infestation assessment and monitoring. In regards to rodent populations, two main areas have been explored in the literature: (1) survey and recognition of rodent infestation; 11,18,19 and (2) automatic identification of rodent evidence, such as burrows, by following a feature‐extraction schema 12,20 . A third group of investigations explores objective assessments of the damaged areas caused by the rodents, but in this case, the research relies on remote sensing, mainly by the use of Moderate Resolution Imaging Spectroradiometer (MODIS) imagery 21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation